Experimental investigation on thermal performance of gravity heat pipe with different pipe configurations - Xing Lu; Jie Liu; Xulei Tong; Renkun Dai; Yang Xiao; Jun Deng (Case Studies in Thermal Engineering)
Gravity heat pipe (GHP) is a critical heat transfer device for enhancing heat transfer efficiency in many fields. The heat transfer performance of GHP is significantly influenced by its pipe configuration. The present study aims at elucidating the impact of pipe configuration on the thermal performance of GHP through experiments. The typical pipe configuration, including conventional vertical inserted straight pipe, oblique inserted straight pipe and curved pipe, were tested and analyzed under equivalent pipe area and equivalent vertical pipe height. It was found that the curved GHPs with equivalent vertical pipe height was the best configuration with optimal curving angle. Following this, a parameter sensitivity analysis using the response surface method was conducted for the curved GHP to further improving its thermal performance. This analysis examined the heat transfer performance of the curved GHP with varied main factors, including evaporator input power (40W, 60W, 80W), filling ratio (20 %, 30 %, 40 %) and curving angle (30°, 45°, 60°). Mathematical correlations are derived for the heat transfer coefficient, thermal resistance, and equivalent thermal conductivity for the curved GHP. The results indicate that the sensitivity ranking for thermal performance of the curved GHP is: input power > filling ratio > curving angle.